2019
DOI: 10.1039/c9ra06559h
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and evaluation of a hierarchical Bi2MoO6/MSB composite for visible-light-driven photocatalytic performance

Abstract: In this study, waste mussel shells were used to remove dyes in aqueous solution. Mussel shell was prepared into mussel shell biochar (MSB), which was used as a carrier to support Bi 2 MoO 6 . A novel Bi 2 MoO 6 /MSB composite photocatalyst was developed by the hydrothermal synthesis method. The as-synthesized sample was characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), N 2 adsorption-desorption method, Fourier transform infrared spectroscopy (FTIR) and UV-vis diffuse reflectance spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Thirdly, Y doping triggered the formation of new defect sites and oxygen vacancies, which acted as electron traps to prevent the recombination of electron-hole pairs. Furthermore, mussel shells, as photocatalyst supports, have unique pores and surface structures which could offer more active sites for pollutant attachment in photocatalytic reactions than stacked catalysts [38,43]. Moreover, shells contained various trace metal elements (e.g., Se, Mn, Zn, Ti, and Sr) that could serve as doping elements, facilitating electron transfer in photocatalytic reactions, thus enhancing the photocatalytic capability of the composites [37,42].…”
Section: Possible Photocatalytic Mechanism Of Photocatalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirdly, Y doping triggered the formation of new defect sites and oxygen vacancies, which acted as electron traps to prevent the recombination of electron-hole pairs. Furthermore, mussel shells, as photocatalyst supports, have unique pores and surface structures which could offer more active sites for pollutant attachment in photocatalytic reactions than stacked catalysts [38,43]. Moreover, shells contained various trace metal elements (e.g., Se, Mn, Zn, Ti, and Sr) that could serve as doping elements, facilitating electron transfer in photocatalytic reactions, thus enhancing the photocatalytic capability of the composites [37,42].…”
Section: Possible Photocatalytic Mechanism Of Photocatalystsmentioning
confidence: 99%
“…The trace metal elements in the shell can act as modifiers to enhance the catalyst's performance [37]. Our previous study has demonstrated that the mussel shell can effectively disperse the photocatalyst and prevent its aggregation, to enhance electron transport and improve the photocatalytic activity [43]. We intended to further enhance the photocatalytic performance of the composite catalyst by doping rare earth elements.…”
Section: Introductionmentioning
confidence: 99%
“…Outstanding structural and mechanical properties of these shelves attracted a significant amount of the scientists worldwide with the goal to utilize them and use for wastewater treatment applications [28,29], for soil remediation [30,31], and as bio-fillers to polymeric matrices [32,33]. Recently, the previous studies demonstrated that waste mussel shells could be prepared into carriers by pyrolysis to support photocatalyst (Bi 2 MoO 6 ) in the application of dyes degradation [34,35]. However, the mussel shells were treated by carbonization at high temperatures to render its large specific surface area, which is confronted with the challenges of high energy consumption and high cost.…”
Section: Introductionmentioning
confidence: 99%